Penatalaksanaan Neuro Development Treatment Pada Kondisi Cerebral Palsy Spastik Atetoid Quadriplegi Di Griya Fisioterapi Bunda Novy Yogyakarta - Debbita, Nurraya Martha, Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Atetoid spastic quadriplegia Cerebral Palsy is a disorder of posture and movement that is uncontrolable, associated with the non-prigressive disorder that occur in the brain during pregnancy and childhood, characterized by fluctuation occurs in muscle tone and stiffness in all four limbs that is the upper limbs and lower limbs. In this case the problems of physiotherapy impairment appears the existence of spasticity in the upper limbs and lower limbs. Physiotherapy modalities used is the method of Neuro Development treatment. Objective: To investigate the management of Neuro-Developmental Treatment on condition of cerebral palsy spastic quadriplegia atetoid to the decrease of spasticity and improvement of functional ability to sit, stand and walk. Results: After 6 times the therapeutic result (1) spasticity that persistent from T1 to T6 measured by asworth scale, the elbow dextra and sinistra obtained a value of 2, the knee dextra and sinistra obtained a value of 2, and the plantar flexor ankle values obtained 1 (2) functional ability as measured by GMFM from T1 to T6 fixed the value obtained persist at 35.63%. Conclusion: Neuro Developmental Treatment (NDT) Management on the condition of cerebral palsy spastic quadriplegia atetoid to decreased levels of spasticity and functional ability to sit, stand and walk has not changed.